Total seed storage protein patterns of some Lathyrus species growing in turkey using SDS-page - Emre, Irfan; Turgut-Balik, Dilek; Genç, Hasan; Şahin, Ahmet (My University, 2010)
Present study determined the variation of total electrophoretic seed protein patterns and protein amounts in some Lathyrus species viz., L. tukhtensis, L. cilicicus, L. saxatilis, L. annuus, L. hierosolymitanus, L. gorgoni var. gorgoni, L. Lycicus and L. odoratus collected from their natural habitats of different localities in Turkey. Electrophoretic data were documented by using a gel documentation system (Bio-Rad, USA) and analysed by using Quantity 1-D analysis software and also the dendogram were formed with 4.0% tolerance in UPGAMA (Unweighed Pair-Group Arithmetic Mean). The differences among species were observed and all 9 taxa were clearly identifiable from the protein patterns. The formed dendogram from SDS-PAGE analysis showed that all studied taxa constituted two clusters. The first one consisted of L. saxatilis, L. gorgoni, L. annuus, L. hierosolymitanus, L. lycicus and L. phaselitanus second one by L. tukhtensis, L. cilicicus and L. odoratus. In cluster I, L. saxatilis and L. gorgoni were found to have higher similarity to each other. Also, it was reproted that quantities of total seed proteins in the present study. L. lycicus (79.906 ?g/ml) has highest total protein content whereas L. cilicicus (65.860 ?g/ml) has lowest total protein content.
Keywords: Lathyrus; Lathyrus annuus; Lathyrus gorgoni; Lathyrus odoratus